ANALISIS IMPLEMENTASI SISTEM INFORMASI DENGAN METODE UTAUT TERHADAP HARAPAN KINERJA (Studi Empiris Penggunaan Single Sign ON pada Mahasiswa FEB UNDIP) - Yaumil Fath; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2023)
This study aims to validate empirically about e-learning which is the context in this research is the use of SSO for students of Faculty of Economics and Business Diponegoro University using UTAUT model. Dependent variabel in this research are use that proxied by perceived usefulness and perceived ease of use, for intervening variabel using attitude towards using and behavioural intentions, Independent variabel using are performance expectancy, effort expectancy, social influence, and facilitating conditions. Sampel selection technique uses purposive sampling and simple random sampling. Path anlysis methods are use to test the hypothesis research. Research findings that effort expectancy has positive significant to attitude towards use and behavioural intentions. Social influence has positive significant to behavioural intentions. Behavioural intentions has positive significant to SSO use. variable of behavioral intention successfully mediates performance expectations on the use of SSO.